Caregivers’ Sense of Coherence and Untreated Dental Caries in Children and Adolescents: A Cross-Sectional Study - Monica Gentil Mattos; Ronir Raggio Luiz; Lucianne Cople Maia; Aline de Almeida Neves (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2023)
Objective: To associate caregivers' sense of coherence (SOC) and untreated caries with oral health status in children covered by a dental public health system. Material and Methods: A convenience sample of caregivers/children in Angra dos Reis, Brazil, was surveyed. Caregivers' SOC was evaluated using the 13-question version questionnaire. For both caregivers/children, sociodemographic information was acquired and caries experience was evaluated by DMFT/dmft and PUFA/pufa index. Statistical associations between children's untreated carious teeth and interest variables from the caregivers were evaluated by binary logistic regression assessed by generalized linear modeling. Results: A total of 233 pairs of caregivers-children were included. Children's untreated permanent and primary carious teeth represented 34.8% and 62.2% of the caries experience, respectively and at least one PUFA/pufa scored tooth was detected in 22.7% of them. Caregivers' DMFT was 13.5±7.0, while 33.6% scored on PUFA. A total of 62.1% of them presented untreated carious lesions. Results from the univariate model, correlating children's untreated caries and caregivers' attributes showed a statistical significance for SOC values (p<0.015), untreated decayed teeth (p<0.035), self-perception of oral health (p<0.022) and oral impact on daily performance (p<0.010). The multivariate logistic first model kept the statistical significance only for the caregiver's untreated decayed teeth. Conclusion: Caregivers' SOC and untreated carious teeth could be used as indicators of dental treatment needs in their offspring.